2019
DOI: 10.1108/ribs-06-2019-0085
|View full text |Cite
|
Sign up to set email alerts
|

The effect of high performance work system strength on organizational effectiveness

Abstract: Purpose This paper aims to examine the implications of high performance work system (HPWS) strength from a managerial perspective and the impact of economic, cultural, political, legal and technological factors on the operationalization of HPWSs in the banking industry in Sri Lanka. Design/methodology/approach The data for this study were collected from three licensed commercial banks in Sri Lanka. This research used a case study approach for data collection with archival analysis of records and semi-structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Previous study has shown a positive effect of work practices on employee, for example Alkhazali et al, (2020) found positive relationship between empowerment, HRM practices and employee outcomes in Jordanian banks. Similarly, Dayarathna, (2019) examine the impact of HPWS on employees effectiveness in Srilankan's banks and found positive correlation. Moreover, Ahmed & Shin, (2019), argued that performance appraisal, selection and recruitment, and compensation HRM practices are positively related with indivdual employee outcomes, in Bangladeshi Banks.…”
Section: High-performance Work Practices and Affective Commitmentmentioning
confidence: 96%
“…Previous study has shown a positive effect of work practices on employee, for example Alkhazali et al, (2020) found positive relationship between empowerment, HRM practices and employee outcomes in Jordanian banks. Similarly, Dayarathna, (2019) examine the impact of HPWS on employees effectiveness in Srilankan's banks and found positive correlation. Moreover, Ahmed & Shin, (2019), argued that performance appraisal, selection and recruitment, and compensation HRM practices are positively related with indivdual employee outcomes, in Bangladeshi Banks.…”
Section: High-performance Work Practices and Affective Commitmentmentioning
confidence: 96%
“…Strong HPWS practice enhances organizational performance (Shih et al, 2006;Zhai and Tian, 2020) and positive outcomes for the organization (economic, cultural, politi-cal, legal, and technological) (Dayarathna et al, 2020) and employees (Abugre and Nasere, 2020). On the other hand, HPWS results in work intensification, increased health harm, and challenges to workplace well-being (Chillakuri and Vanka, 2021).…”
Section: High-performance Working System (Hpws)mentioning
confidence: 99%
“…Understanding entrepreneurship today necessitates the consideration of non-material variables, such as human resources, culture, social networks and social capital, along with material factors (Dayarathna et al, 2019). In this study, the entrepreneurship performance and potential of Turkey and 10 Balkan countries were evaluated in connection with material factors such as technology and competition as well as social characteristics such as culture and human resources.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%